Societal threat as a moderator of cultural group selection. (9th March 2016) - Gelfand, Michele J.; Roos, Patrick; Nau, Dana; Harrington, Jesse; Mu, Yan; Jackson, Joshua
Abstract: As scholars have rushed to either prove or refute cultural group selection (CGS), the debate lacks sufficient consideration of CGS's potential moderators. We argue that pressures for CGS are particularly strong when groups face ecological and human-made threat. Field, experimental, computational, and genetic evidence are presented to substantiate this claim.